Using enzyme activities as an indicator of soil fertility in grassland - an academic dilemma - Wang, Li; Hamel, Chantal; Lu, Peina; Wang, Junying; Sun, Dandi; Wang, Yijia; Lee, Soon-Jae; Gan, Gary Y. (Frontiers in Plant Science, 2023)
Grasslands play an important role in conserving natural biodiversity and providing ecosystem functions and services for societies. Soil fertility is an important property in grassland, and the monitoring of soil fertility can provide crucial information to optimize ecosystem productivity and sustainability. Testing various soil physiochemical properties related to fertility usually relies on traditional measures, such as destructive sampling, pre-test treatments, labor-intensive procedures, and costly laboratory measurements, which are often difficult to perform. However, soil enzyme activity reflecting the intensity of soil biochemical reactions is a reliable indicator of soil properties and thus enzyme assays could be an efficient alternative to evaluate soil fertility. Here, we review the latest research on the features and functions of enzymes catalyzing the biochemical processes that convert organic materials to available plant nutrients, increase soil carbon and nutrient cycling, and enhance microbial activities to improve soil fertility. We focus on the complex relationships among soil enzyme activities and functions, soil microbial biomass, soil physiochemical properties, and soil/crop management practices. We highlight the biochemistry of enzymes and the rationales for using enzyme activities to indicate soil fertility. Finally, we discuss the limits and disadvantages of the potential new molecular tool and provide suggestions to improve the reliability and feasibility of the proposed alternative.